STRATEGY OF PERFORMANCE-BASED HUMAN RESOURCES DEVELOPMENT IN CIVIL APPARATUS OF THE LOCAL GOVERNMENT OF CENTRAL SULAWESI PROVINCE - Armida; Hasanuddin, Bakri; T, Muzakir (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2025)
The purpose of this study was to determine and analyze the efforts implemented by regional apparatus in developing performance-based human resources that can be applied to ASN of the Central Sulawesi Provincial Government and to analyze the factors that inhibit the strategy of developing performance-based human resources that can be applied to ASN of the Central Sulawesi Provincial Government. This study was conducted for 3 months. Research method. The research method uses qualitative descriptive through a survey approach. The study was conducted in three regional apparatuses with the lowest public satisfaction index values ​​of the Central Sulawesi provincial government in 2023, namely the Regional Disaster Management Agency (BPBD), the Civil Service Police Unit (Satpol PP) and the Development Administration Bureau. The data collection method was carried out by means of interviews, observations and documentation with informants who were the sources in this study. The data analysis technique used in this study was by using the assistance of the NVivo program. The results of the study showed that the results of the study showed that efforts to develop human resources based on ASN performance were carried out in two ways, namely formal and informal methods. Factors that hinder the implementation of human resource development based on ASN performance are costs or budgets, limited human resources such as lack of interest and enthusiasm for participating in training and inadequate equipment.